Developing a MOOC: Factoring disability - Kent, Michael; Smith, L.; Dowse, L.; Soldatic, K. (2017)
However, the uptake of MOOCs has plateaued. This is the first volume that addresses Massive Open Online Courses from a post-MOOC perspective.